Analisis Potensi Dan Implementasi Pembangkit Listrik Tenaga Surya (PLTS) Dalam Mendukung Sistem Transportasi Di Bali - I Wayan Yudi Martha Wiguna; Aris Budi Sulistyo; Rahmat Ahmad; Hendrik Prasetyo (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2026)
This study aims to investigate the potential and implementation of Solar Power Plants (SPP) in supporting the transportation system in Bali. As a region with high solar radiation and a tropical climate, Bali has significant potential to utilize solar energy as a source of electricity. However, the utilization of solar energy in Bali remains far below the average of countries that have widely adopted solar power technologies. This research employs a three-stage methodology consisting of field surveys, weather data modeling, and environmental impact analysis. Field surveys are conducted to collect solar radiation data from various locations in Bali, while weather data modeling using PVGIS is applied to estimate solar energy potential. Environmental impact analysis includes the evaluation of potential impacts on water, air, and soil resulting from the implementation of solar power plants, making the study comprehensive and holistic. The results of this study are expected to provide projections of the energy that can be generated by solar power plants in several regions of Bali. Furthermore, the implementation of solar power plants is expected to contribute to the reduction of CO₂ emissions. To encourage the development of solar power plants in Bali, supportive policies and regulations, as well as active participation from government institutions, investors, and local communities, are essential. With appropriate support, the development of solar power plants in Bali can become an effective solution to meet energy demands while promoting long-term energy and environmental sustainability.